Attitudinal barriers to buprenorphine prescription and former waiver training - Gannon, Michael P.; Tello, Monique; Wakeman, Sarah; Charles, Jean-Pierre; Lipsitz, Stuart; Samal, Lipika (Journal of Opioid Management, 2024)
Objective: Opioid use disorder (OUD) can be effectively treated with buprenorphine maintenance. Recent changes in federal policy have removed the requirement for physicians to complete additional training to apply for a Drug Enforcement Administration (DEA) waiver to prescribe buprenorphine. At that time, few primary care providers (PCPs) had completed the training for a DEA waiver to prescribe buprenorphine. Our goal was to identify addressable barriers that may persist despite updates to federal legislation. Design: A 42-item survey was distributed to 662 physicians and nurse practitioners at two academic medical centers with 100 respondents. Setting: The survey was sent via email and administered anonymously through SurveyMonkey. Patients and participants: All participants were PCPs, and all PCPs at the two academic medical centers were eligible to participate. Interventions: PCPs responded to the survey by answering questions online. Main outcome measures: PCPs answered questions regarding previous buprenorphine waiver training status, local OUD prevalence, the effectiveness of OUD treatment modalities, and previous barriers to training. Results: Respondents were compared using descriptive statistics and logistic regression. Of the 100 respondents (response rate: 15 percent), 69 percent had not completed the training. Ninety-nine percent of PCPs agreed that OUD was an issue in their area, 94 percent saw patients with OUD, and 91 percent rated buprenorphine maintenance as a very effective treatment for OUD. Previously waivered and nonwaivered providers did not differ in their responses to these questions. Those who had been waivered were less likely to say they did not see enough patients with OUD to justify training (odds ratio [OR] 0.267, p = 0.005) and were less likely to express concern about allowing patients with OUD into their practice (OR 0.348, p = 0.020) than PCPs who had applied for the DEA waiver. Conclusions: Despite nonwaivered PCPs recognizing OUD’s prevalence, they were concerned about allowing patients with OUD into their practice and said there were not enough patients to justify training. This suggests that attitudinal barriers are the most appropriate target for current intervention.